2014
DOI: 10.1016/j.nlm.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the rapid transcriptional response to long-term sensitization training in Aplysia californica

Abstract: We used a custom-designed microarray and quantitative PCR to characterize the rapid transcriptional response to long-term sensitization training in the marine mollusk Aplysia californica. Aplysia were exposed to repeated noxious shocks to one side of the body, a procedure known to induce a longlasting, transcription-dependent increase in reflex responsiveness that is restricted to the side of training. One hour after training, pleural ganglia from the trained and untrained sides of the body were harvested; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…This is considerably less than the 1494 transcripts we found regulated immediately after long-term sensitization training using the same array platform, tissue sample, sample size, and statistical criteria (Herdegen et al 2014). The most likely explanation is a difference in statistical power due to different experimental designs.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…This is considerably less than the 1494 transcripts we found regulated immediately after long-term sensitization training using the same array platform, tissue sample, sample size, and statistical criteria (Herdegen et al 2014). The most likely explanation is a difference in statistical power due to different experimental designs.…”
Section: Discussionmentioning
confidence: 71%
“…We used the treat function from limma (McCarthy and Smyth 2009) to conduct two separate tests of significance: (1) against the standard null hypothesis of no regulation (H o : mean fold change ,1 or .1; note that a ratio of 1 is produced when both trained and untrained samples have the same levels of gene expression) and then (2) against a null of at least 1.1-fold change in either direction. We have found that transcripts regulated by this more stringent criterion are likely to generalize to an independent sample (Herdegen et al 2014).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations